The Earth is all that lasts : [large type] Crazy Horse, Sitting Bull, and the last stand of the Great Sioux Nation - Gardner, Mark Lee, 1960- (Harper Large Print, 2022)
"A magisterial dual biography of Crazy Horse and Sitting Bull, the two most legendary and consequential American Indian leaders, who triumphed at the Battle of Little Bighorn and led Sioux resistance in the fierce final chapter of the "Indian Wars." Crazy Horse and Sitting Bull: Their names are iconic, their significance in American history undeniable. Together, these two Lakota chiefs, one a fabled warrior and the other a revered holy man, crushed George Armstrong Custer's vaunted Seventh Cavalry. Yet their legendary victory at the Little Big Horn has overshadowed the rest of their rich and complex lives. Now, based on years of research and drawing on a wealth of previously ignored primary sources, award-winning author Mark Lee Gardner delivers the definitive chronicle, thrillingly told, of these extraordinary Indigenous leaders. An essential new addition to the canon of Indigenous American history and literature of the West, The Earth Is All That Lasts is a grand saga, both triumphant and tragic, of two fascinating and heroic leaders struggling to maintain the freedom of their people against impossible odds" --Provided by publisher.